Faktor-Faktor Penentu Profitabilitas Return On Average Asset Pada Bank Umum Yang Terdaftar Di Bursa Efek Indonesia (BEI) [Determinants of Profitability of Return on Average Assets of Commercial Banks Registered in Indonesian Stock Exchange (IDX)] - Viladelva Vio Vieresta Saras Manu (Universitas Pelita Harapan, 2022)
This study was conducted to determine the determinants of the profitability of return on average bank assets such as size, capad, bcost, and risk in 46 commercial banks in CapitalIQ with a monthly period in the period 2010–2020. The data analysis methods used are chow test, hausman test, langrage multiplier test, as well as diagnostic tests (heterokedasticity test, classical assumption test and cycling test). The results of this study show that (1) Size has no impact because it is not significant to the profitability of return on average assets (2) Capad has no impact because it is not significant to the profitability of return on average assets (3) Bcost has a negative but significant impact because affects the increase in profitability of return on average assets and (4) Risk has no impact and is not significant on the profitability of return on average assets.BAHASA INDONESIA ABSTRACTPenelitian ini dilakukan untuk mengetahui faktor-faktor penentu profitabilitas return on average asset bank seperti size, capad, bcost, dan risk pada 46 bank umum yang terdapat di CapitalIQ dengan jangka waktu bulanan dalam kurun waktu 2010–2020. Metode analisis data yang digunakan yaitu uji chow, uji hausman, uji langrage multiplier, serta uji diagnostik (uji heterokedastisitas, uji asumsi klasik dan Uji pesaran). Hasil penelitian ini menunjukkan bahwa (1) Size tidak berdampak karena tidak signifikan terhadap profitabilitas return on average asset (2) Capad tidak berdampak karena tidak signifikan terhadap profitabilitas return on average asset (3) Bcost berdampak negatif tetapi signifikan karena mempengaruhi kenaikan profitabilitas return on average asset, dan (4) Risk tidak mempunyai dampak dan tidak signifikan terhadap profitablitas return on average asset.